The Challenge of Preserving Digital Maps - Stenvall, Jani (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
This paper addresses some general matters on the preservation of different types of digital materials. The well-known technical problems are explained and also some of the usual strategies to resolve these problems. Digital maps and their preservation is considered in the light of the future legal deposit act in Finland.